Understanding spatial media - Kitchin, Rob,; Lauriault, Tracey P.,; Wilson, Matthew W., 1981- (SAGE Publications Ltd, 2017)
Over the past decade, a new set of interactive, open, participatory and networked spatial media have become widespread. These include mapping platforms, virtual globes, user-generated spatial databases, geodesign and architectural and planning tools, urban dashboards and citizen reporting geo-systems, augmented reality media, and locative media. Collectively these produce and mediate spatial big data and are re-shaping spatial knowledge, spatial behaviour, and spatial politics. Understanding Spatial Media brings together leading scholars from around the globe to examine these new spatial media, their attendant technologies, spatial data, and their social, economic and political effects. The 22 chapters are divided into the following sections: . Spatial media technologies . Spatial data and spatial media . The consequences of spatial media Understanding Spatial Media is the perfect introduction to this fast emerging phenomena for students and practitioners of geography, urban studies, data science, and media and communications.